42x/5-72=6x+84

Simple and best practice solution for 42x/5-72=6x+84 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42x/5-72=6x+84 equation:



42x/5-72=6x+84
We move all terms to the left:
42x/5-72-(6x+84)=0
We get rid of parentheses
42x/5-6x-84-72=0
We multiply all the terms by the denominator
42x-6x*5-84*5-72*5=0
We add all the numbers together, and all the variables
42x-6x*5-780=0
Wy multiply elements
42x-30x-780=0
We add all the numbers together, and all the variables
12x-780=0
We move all terms containing x to the left, all other terms to the right
12x=780
x=780/12
x=65

See similar equations:

| x-3x-2=18 | | 195/x=4 | | 195÷x=4 | | 28=-y/5 | | 19,5÷x=0,4 | | x²-5x+13=0 | | 19.5÷x=0,4 | | 7x/3+8=2x/3 | | 8x+10-5+5-x=55-10 | | 3+x=21-4x | | 7.1x(600+50)+2=x | | 7.1x(600+50)+2=4617 | | 7.1x(600+50)+2=6812.5 | | 7.1x(600+50)+2=10.9 | | -30=14+x. | | x4+8x2-48=0 | | -6k+1=-+7k | | 8x-1=6x+25 | | (81)^-4÷(729)^2-x=9^4x | | 5a+2=-9a+8 | | 3(6c+1)=75 | | -6(k-6)=6k | | -13+37=-2(x+3) | | (2y+4)+(3y-65)=y | | 6.q-2=16 | | 4.m+1=33 | | 2x+1/6-4x-2/9=5/3 | | 2(x+16=48) | | 2(x+16=48 | | 4(3x+7)=-21+1 | | 15x^-2=30+24x-4x^2 | | x^2/3=120 |

Equations solver categories